Entomophagus Response of Indigenous Chicken to Diets Enriched with German Cockroach (Blattela germanica) Meal in Kenya - Ngaira, Victor Muhumbwa; Wambui, Caroline Celina; Mosi, Reuben Oyoo; Wayua, Francis Obuoro; Wachira, Anne Mumbi; Ilatsia, Evans Deyie (East African Journal of Agriculture and Biotechnology, 2023)
Feeding accounts for 65-70% cost of production in a chicken enterprise. Fishmeal has primarily been used as a source of protein in chicken feed owing to its excellent nutritional value. However, due to its unstable supply and variation in quality, recent studies have focused on finding alternative protein feedstuff, such as edible insects. A study was carried out to evaluate the effects of substituting fishmeal (FM) with Blattela germanica meal (BGM) on the growth of chicks. Seventy-two KALRO improved indigenous chickens (KC), at the grower stage, eight weeks old, comprising an equal number of males and females were used as sampling units in a completely randomized design (CRD) feeding trial. Each of the four treatments was replicated three times. Birds were fed on dietary treatments that were isocaloric and isonitrogenous and comprised - treatments TA (87.5 %FM, 12.5% BGM), TB (62.5 % FM, 37.5 % BGM), and TC (50% FM, 50% BGM) TD (100 %FM, 0% FM) Control. Data on daily feed intake and weekly live weight was taken for eight weeks and used to calculate the Feed conversion ratio (FCR) and average daily gain (ADG). Data were subjected to a one-way analysis of variance (ANOVA). The feed intake, average daily gain, final weight gain, and feed conversion ratio was not significantly different from the control (P> 0.05). Thus, indigenous chicken fed diet with BGM and fishmeal performed similarly. As such, farmers should be encouraged to incorporate cockroaches as their on-farm feed to reduce the feed cost and increase chicken productivity.
Keywords: Cockroach Meal; Chicken; Feed; Intake; Kenya